(untitled) (Health Renaissance, 2014)
We report a case of a 27 year old male with heart shaped itchy, erythematous scaly lesions with well defined margin on lower abdomen for 6 weeks with history of similar skin complaint in spouse since 3 months. Patient got married 4 months back. DOI: http://dx.doi.org/10.3126/hren.v11i3.9654 Health Renaissance 2013;11(3):279-280